Nursing professionals' knowledge regarding the management of waste produced in primary health care - Matheus Costa Brandão Matos (Revista Brasileira de Enfermagem)
ABSTRACT Objective: To evaluate the knowledge of Nursing professionals regarding waste management in primary healthcare services. Method: Descriptive study with a mixed approach, developed with 42 nursing professionals who worked in basic health units of a capital in the Brazilian Northeast Region. Quantitative variables were analyzed by the SPSS 20.0 program. Reports were processed by the IRaMuTeQ software, analyzed according to the descending hierarchical classification, and grounded on the Collective Subject Discourse. Results: Low knowledge scores were obtained, associated with specific socioeconomic and training variables. Analysis of collected reports allowed to identify three classes: "Inadequate waste disposal: first and main step"; "Correct disposal improves service quality and prevents diseases"; and "Consequences associated with incorrect disposal". Conclusion: The knowledge of professionals falls short of the expectations to adequately manage waste produced in primary health care and is concentrated on the initial steps, mainly the disposal process.